Estimation of de-passivation period of steel in concrete based on chloride diffusion tests - Prabakar, J.; Manoharan, P. Devadas; Neelamegam, M.; Iyer, Nagesh R (Journal of Structural Engineering, 2025)
Reinforced cement concrete is one of the best composite material for almost all the civil engineering building structures due to its economical, feasible and easy mouldability. Earlier days, concrete strength was a significant decisive factor for design of any structure. But now a days, concrete of High strength (HC) with High Performance is essential to have more service life. The service life of any structure is very important at design stage particularly with relation to environment factor. Therefore, experimental studies have been carried out to establish a relationship between Rapid Chloride Ion Penetration Values and Chloride Ion diffusion values. From these, the life of the RCC structure will be determined. For the purpose, around 40 types of concrete mixes have been selected which includes, concrete grades of M25, M35, M40, M60 and M75 with and with out mineral admixtures and determined RCPT and Chloride diffusion co-efficient values by conducting Rapid Chloride Ion Penetration test (RCPT) and Chloride diffusion co-efficient by steady state method. A correlation between the two values is established using which the time required for de-passivation of reinforcement is predicted for different concrete mixtures.